Effects of beta-hydroxy-beta-methylbutyrate supplementation on strength and body composition in trained and competitive athletes: A meta-analysis of randomized controlled trials - Sanchez-Martinez, J.; Santos-Lozano, A.; Garcia-Hermoso, A.; Sadarangani, K. P.; Cristi-Montero, C. (Journal of Science and Medicine in Sport, 2018)
Objectives: The aim of this meta-analysis was to examine the evidence for the effectiveness of beta-hydroxy-beta-methylbutyrate supplementation interventions on modification in strength and body composition in trained and competitive athletes. Design: Systematic review and meta-analysis. Methods: A systematic search was performed using three databases: MEDLINE, EBSCO and Web of Science. The analysis was restricted to randomized controlled trials that examined the effect of HMB supplementation interventions on modification in bench and leg press strength, body mass, fat-free mass and fat mass. Effect sizes (ES) and 95% confidence intervals (CIs) were calculated using a fixed effect meta-analysis due to low value of the heterogeneity. The Egger test was used to determine the presence of publication bias, and the Q and I2 statistics were used to assess heterogeneity among studies. Significance was set at p < 0.05. Results: Six studies were selected for meta-analysis, as they fulfilled the inclusion criteria (n = 193 participants). HMB supplementation interventions present a trivial non-significant ES in all variables studied (bench press ES = 0.00, leg press ES = 0.09, body mass ES = -0.01, fat-free mass ES = 0.16, and fat mass ES = -0.20; all cases p > 0.05, and null heterogeneity I2 = 0.0% p > 0.05). These results remained constant even analyzing by subgroups (HMB doses, duration of intervention, training level and diet co-intervention). Conclusions: This meta-analysis found no effect of HMB supplementation on strength and body composition in trained and competitive athletes.